ALTERNATIF PENYELESAIAN SENGKETA, KEPASTIAN DAN PERLINDUNGAN HUKUM - Ahmad Gozali (LP3M STIH Painan, 2016)
In bussiness relation ship or contrct always be raising conflict. The conflict which is necessary anticipated is how the way to implement contracting clauses, whether that is contract or caused by the other matter. In many civil contracts, arbitary clauses many a used as choice of solution of conflict. Law opinion which is stated by Institute of Arbitation is binding because the stated opinion will become portion wittr is separated from meant contract (with is asked for opinion at the Institute of eruitrution). Every contrary opinion over is with given taw opinion, that is meant offense to the contact (This is default or breaking confract). Therefore it can not be enforced resistance in what ever power of law. Arbitary decision in independent, finally and binding (like decision with as permanent low power) so that chairman or court is not permitted to examine reason or the national consideration of decision of arbitration. The court has now power to re examine lawsuit which had been stated its arbitrary decision, except there is action against the linked law by taking adjudication of arbitration in good will, and when the arbitrary adudication offend as public order